A Brief Review on Prospective of Polyvinylidene Fluoride as a Tissue Engineered Scaffold Material - Hamzah, Mohd Syahir Anwar; Razak, Nurul Amira Ab; Ng, Celine; Sukor, Jumadi Abdul; Razak, Saiful Izwan Abd; Mat Nayan, Nadirul Hasraf (Journal of Advanced Industrial Technology and Application, 2020)
: This review focuses on the potential of polyvinylidene fluoride (PVDF) as tissue scaffolding materials. PVDF is defined in terms of the synthesis mechanisms and the method of the Î² phase formation process. General properties are fundamentally discussed in terms of their wettability and electroactive characteristics, which play an important role in the modification of other potential materials for tissue-based applications. The latest technologies for the replacement of artificial tissue scaffolds are evaluated and the applications of PVDF-based scaffolds are discussed.